Digital Option Pricing Approach Using A Homotopy Perturbation Method - Amirul Hakam; Islachiyatul Ummah; Frida Akbar Rani; Nur Asiyah; Endah RM. Putri ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2021)
An option is a financial contract between buyers and sellers. The Black-Scholes equation is the most popular mathematical equation used to analyze the option pricing. The exact solution of the Black-Scholes equation can be approached by several approximation methods, one of the method is a Homotopy Perturbation Method (HPM). The simplest type of option, digital options were analyzed using the HPM. The digital option pricing approach using the HPM is in a power series form, which in this paper is presented the solution in the fourth power. This solution is compared with the exact solution of the Black-Scholes equation for digital options. The results show that the approach using HPM is very accurate.